Abstract 092: Vasospasm as a Consequence of IVIg Usage for GBS. - Connor D Welsh (Stroke: Vascular and Interventional Neurology)
Introduction The relationship between Intravenous Immunoglobulin (IVIg) and cerebrovascular vasospasm is poorly and incompletely understood. Some case reports have identified IVIg as potential therapy for vasospasm, while others have implicated it as a causative agent in primarily coronary artery vasospasm and the development of atypical angina. This case illustrates a situation in which a patient with Guillain‐Barre Syndrome (GBS) was started on IVIg and developed subsequent vasospasm with cerebral infarcts requiring intra‐arterial therapy. Methods Case Report Results Our patient is a 62 year old female with a history of cervicothoracic subdural hematoma status postevacuation with left leg weakness, hypertension, known right ICA aneurysm, and chronic left ICA occlusion who presented as a transfer from an outside facility where she initially presented with progressive back pain, lower extremity weakness, areflexia and dysautonomia. MRI brain initially demonstrated posterior‐predominant T2 hyperintensities affecting subcortial white tracts suggestive of PRES. Lumbar puncture demonstrated cytoalbuminologic dissociation supporting a superimposed GBS. IVIg was initiated, however the patient's mentation and examination declined. Repeat MRI demonstrates bilateral, posterior‐predominant acute multifocal ischemic infarcts. Vessel imaging demonstrated vasospasm of the basilar and bilateral anterior Circle of Willis. Oral Verapamil was initiated. Digital Subtraction Angiography confirmed these findings; intra‐arterial verapamil was utilized with significant improvement in the patient's examination. Conclusion IVIg has only a weak association with coronary artery vasospasm, however is heavily implicated in the onset of this patient's diffuse vasospastic ischemic disease. Prompt identification and aggressive initiation of treatment is essential in minimizing the burden of ischemic stroke and optimizing outcomes for these complex patients.